Time-Restricted Feeding Reinforces Gut Rhythmicity by Restoring Rhythms in Intestinal Metabolism in a Jetlag Mouse ModelSummary - Hui Leng; Theo Thijs; Louis Desmet; Guillaume Vanotti; Mona Farhadipour; Inge Depoortere (Cellular and Molecular Gastroenterology and Hepatology)
Background & Aims: Circadian disturbances result in adverse health effects, including gastrointestinal symptoms. We investigated which physiological pathways in jejunal mucosa were disrupted during chronic jetlag and prevented during time-restricted feeding (TRF). Enteroids from Bmal1+/+ and Bmal1-/- mice were used to replicate the processes that were affected by chronic jetlag and rescued by TRF. Methods: C57BL/6J male mice were subjected to chronic jetlag or night-TRF for 4 weeks. An around-the-clock bulk-RNA sequencing study was performed on the jejunal mucosa. Bmal1+/+ and Bmal1-/- mouse enteroids were generated to study the jejunal epithelial clock dependency of rhythmic jejunal processes. Results: Chronic jetlag disrupted the rhythmicity of jejunal clock genes and the jejunal transcriptome, which was partially rescued by TRF. Genes whose rhythm was altered by chronic jetlag but prevented by TRF were primarily associated with nutrient transport, lipid metabolism, ketogenesis, and cellular organization. In vivo, chronic jetlag caused a phase shift in the rhythmic accumulation of neutral lipids and induced a diurnal rhythm in the number of crypt epithelial cells, both of which were prevented by TRF. In vitro, enteroids replicated the in vivo rhythmic accumulation of neutral lipids in a clock-dependent manner, whereas the rhythm of S phase proliferation was ultradian in both genotypes of enteroids. Conclusions: This pioneering transcriptomic study demonstrates that TRF acts as a robust entrainer during chronic jetlag, realigning disturbances in the circadian clock and the transcriptome involved in metabolic functions in the jejunal mucosa. Enteroids can replicate the rhythmic accumulation of neutral lipids dependent on the jejunal epithelial clock, enabling these functions to be studied in vitro.